Diversity in antioxidant properties and mineral contents of Allium paradoxum in the Hyrcanian forests, Northern Iran - SEDIGHEH KHODADADI; TAHER NEJADSATTARI; ALIREZA NAQINEZHAD; MOHAMMAD ALI EBRAHIMZADEH (Biodiversitas Journal of Biological Diversity, 2015)
Khodadadi S, Nejadsattari T, Naqinezhad A, Ebrahimzadeh MA. 2015. Diversity in antioxidant properties and mineralcontents of Allium paradoxum in the Hyrcanian forests, Northern Iran. Biodiversitas 16: 281-287. The knowledge about variation ofantioxidant properties from local medicinal plant can be achieved by investigating all natural habitats of it. To reach this goal, acomprehensive survey on eight populations of Allium paradoxum (M. B.) G. Don, was conducted in the Hyrcanian forests. A.paradoxum (Amaryllidaceae) is a perennial, local plant, native to the northern Iran. Different parts of it, is largely used in foodpreparation and traditional medicine. Plants were collected randomly from different altitudes and forest sites of Iranian northernprovinces ranging from west to east (Guilan, Mazandaran and Golestan Provinces). Samples were divided into aerial and bulbous parts.The antioxidant activities of the extracts were investigated with 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and reducing power assays.Total flavonoid content was determined by a colorimetric aluminum chloride method. The highest antioxidant activities and flavonoidcontents in A. paradoxum were related to Varaki and Zarinabad sites (Mazandaran province) with relatively higher humidity, in thecentral part of the Hyrcanian area and in altitudinal range between 462-860 m asl. The content of total phenolics in the extracts wasdetermined according to the Folin-Ciocalteu reagent method, and calculated as gallic acid equivalents (GAE). With respect to totalphenolic contents, aerial parts of plants of Jahannama, the lowest elevation site (Golestan province), had the highest amount. Elementalcomposition (Fe++, Mn++) and total sulphur were also determined using Atomic Absorption Spectroscopy and digestion method,respectively. Higher contents of two elements, particularly Fe, and total sulphur can be found in bulbous part of Zarinabad and Kiasarpopulations (Mazandaran province) compared to other sites. The results of the current study indicated that there is a remarkable andsignificant variation of antioxidant activities among different studied populations of A. paradoxum in the Hyrcanian forests.